Sleep problems in cancer: effective psychological interventions – a systematic review (Res Medica, 2014)
Introduction: Sleep problems are one of the most prevalent complications cancer patients experience. These have been shown to produce harmful effects such as reduced immunity and mood disturbances. While pharmacological agents for sleep problems may be used, psychological therapies should be considered where possible.Aim: The aim of this review is to evaluate the effectiveness of different psychological interventions for sleep problems in cancer patients.Methods: A systematic review was conducted. Databases searched included PsychINFO, Embase, MEDLINE, and Web of Science for papers published during the period from January 2003 to December 2013. Combinations of the following terms were used: “sleep disturbance”, “sleep problems”, “insomnia”, “cognitive behavioural therapy”, “CBT”, “non-pharmacological”, “sleep hygiene”, “psychological intervention”, “psychological treatment”, and “cancer”.Results: 22 papers were selected for analysis. The main finding from this systematic review was that cognitive behavioural therapy (CBT) and mindfulness-based stress reduction (MBSR) is the most promising psychological intervention for the treatment of insomnia in cancer patients. Other psychological treatments such as sleep education and multimodal programmes also demonstrate good potential for use in oncology.Conclusions: Further randomized controlled trials comparing the effectiveness of CBT and MBSR in different types of cancer are required to determine their relative benefits and costs.